Microscopy Driven Characterization of Human Brown Adipose Spheroids. - Sajjad, Aima (My University, 2026)
Brown adipose tissue (BAT) is an adipose tissue (AT) that dissipates chemical energy as heat through uncoupling protein 1 (UCP1). It contributes to metabolic health through improved glucose homeostasis, insulin sensitivity, and protection against obesity-related dysfunction. Due to this, there is growing interest in developing physiologically relevant human in vitro models to study its biology. In this thesis, a novel 3D spheroid model of human BAT was established using primary human brown adipocytes. To assess whether the model reproduces key BAT features, differentiated (DIFF) brown adipose (BA) spheroids were compared with undifferentiated (UND) BA spheroids and DIFF white adipose (WA) spheroids using BAT and white adipose tissue (WAT) samples from three patients. Immunofluorescence staining for UCP1, Perilipin-1 (PLIN1), and CD31 were combined with a viability assay and transmission electron microscopy (TEM). Quantitative image analysis was performed in Fiji/ImageJ using a reproducible pipeline. The results showed that DIFF BA spheroids displayed BA-like features compared with UND BA spheroids, with an average UCP1-positive area fraction of 27.8% and 0% respectively. In contrast, WA spheroids showed low UCP1 signal, while UND BA spheroids showed none. TEM confirmed abundant mitochondria and multilocular lipid droplet morphology in DIFF BA spheroids. For viability assessment, an average percentage of 91.6% was quantified for BA spheroids, further supporting structural stability. CD31 positivity was low in all groups, as expected due to the absence of endothelial cells. Overall, this work establishes a primary human 3D BA spheroid model that captures structural and phenotypic hallmarks of BAT and provides a strong foundation for translational studies.
Keywords: Brown Adipose Tissue; Thermogenesis; Uncoupling Protein 1; Spheroids; Image Analysis; 3D-Cell Culture Techniques.